Recommendation system for mood stabilization using content recommendation - Al-Wakil, Kazi Md.; Rahman, Rifai; Nawal, Nafisa; Meem, Sababa Rahman; Rashid, Sajid (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.